Phytochemical Constituents and Pharmacological Potential of Justicia gendarussa Burm. f.: A Review - Annisa Nofriani; Naura Nurnahari (Lembaga Pengembangan Kinerja Dosen, 2025)
Justicia gendarussa Burm. f., commonly known as gandarusa, is a medicinal shrub widely distributed in South and Southeast Asia. Traditionally, it has been used for treating rheumatism, headache, asthma, bronchitis, skin infections, and as a male contraceptive. Phytochemical analyses revealed the presence of alkaloids (gendarusin A, gendarusin B), flavonoids (quercetin, kaempferol, apigenin), saponins, tannins, phenolics, terpenoids, and Patentiflorin A, a compound with promising anti-HIV activity. Pharmacological investigations demonstrated its anti-inflammatory, analgesic, antimicrobial, antioxidant, antidiabetic, hepatoprotective, immunomodulatory, anticancer, and contraceptive potentials. This review highlights the phytochemical profile, pharmacological properties, and future prospects of J. gendarussa, emphasizing its potential as a phytopharmaceutical candidate. Further studies are required to standardize extracts, confirm clinical efficacy, and ensure long-term safety.